PENGARUH BERMAIN GAME ONLINE TERHADAP KOMUNIKASI INTERPERSONAL PESERTA DIDIK KELAS XI DI SMA NEGERI 3 KOTA PARIAMAN - Fitri Dwi Hanifah; Mori Dianto; Rahmawati Wae (STKIP Pesisir Selatan, 2026)
This research is motivated by the phenomenon in the field, namely several students who often play games, and do not show empathetic responses, seem to have difficulty establishing two-way communication, and often do not focus when invited to discuss or collaborate. The purpose of this study is to see: 1) the description of playing online games in students, 2) the description of interpersonal communication in students, 3) the effect of playing online games on interpersonal communication in students. This type of research is quantitative correlational research. The study population was 318 people, with a purposive sampling technique so that the sample was 116 people. The instrument used was a questionnaire, the data analysis technique in the study was simple linear regression analysis. Based on the research, the following results were obtained: 1) the description of playing online games by students is in the high category, 2) the description of interpersonal communication by students is in the poor category, 3) there is a significant influence of playing online games on interpersonal communication by 59.6% with a fairly strong category. Therefore, it is recommended for BK teachers to provide guidance and counseling services related to the management of playing online games and the development of interpersonal communication skills of students.